Pengaruh Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian melalui Peran Mediasi Citra Merk di McDonald's Palangkaraya - Budiman Bancin, John; Eka Damayanti, Nurlia; Aprilita, Aprilita; Josefina Novalina Banurea, Joice (Jurnal Manajemen dan Organisasi, 2023)
Business development requires companies to have a competitive advantage in order to compete with their competitors. Nowadays, consumers are more selective in making purchases to fulfil their needs and desires. Therefore, it is important for companies to implement marketing strategies that are oriented towards competitive advantage in order to attract potential market. Based on research conducted by the Frontier Consulting Group, it is known that McDonald's Top Brand Index (TBI) is ranked 2nd with the TBI value of 25.40%. McDonald's is still below its competitor KFC with the TBI value of 27.20%. The top brand index is an indicator of a brand's performance based on 3 criteria in its assessment, namely mind share, market share and commitment share. This study aims to determine the effect of promotion and service quality on purchasing decisions at McDonald’s Palangka Raya with brand image as the intervening variable. The sampling technique in this study uses the Cochran formula so that the sample size was obtained 100 respondents. The results showed that promotion, service quality and brand image each had a positive and significant effect on purchasing decisions at McDonald’s Palangka Raya. Then, in the mediation test, brand image didn’t become the intervening variable and was unable to mediate variable promotion and service quality in this research model.